Gamification’s efficacy in enhancing students' HTML programming skills and academic achievement motivation - Alsuhaymi, Dhaifallah Saleh; Alotaibi, Ohood Mohammed (Journal of Education and e-Learning Research, 2023)
This study aims to demonstrate the efficacy of gamification in developing HTML programming skills and academic achievement motivation for 10th-grade students. Despite the significance of computer programming in developing students' thinking, many students still need more motivation to learn it. One of the entertaining strategies of computer programming is gamification. The study used a quasi-experimental design for two groups. The experimental group (N=18) was taught by gamification and the control group (N=17) was taught by the traditional teaching method. The researcher conducted a pre-test to determine the equivalence between groups using a valid and reliable practical test and scale. After three-weeks of teaching, the same test and scale were applied to compare the groups. The result showed statistical differences between the two groups in favor of the experimental group in programming skills and all academic achievement motivation dimensions. This study recommended that using gamification in teaching programming languages to students at different stages would help computer teachers. More research should be conducted to investigate the impact of gamification on teaching different programming languages.